Seasonal mobility of boron and salt in relation to rainfall across the growing season - Farr, H.; Bennett, Sarita (Australian Society of Agronomy, 2012)
Boron and salinity are serious constraints to cropping around the world and commonly occur together. Cropping on boron and saline toxic land is restricted by the low tolerance of crops to these abiotic factors, especially as stresses are highest at the start and end of the growing season. The aim of this study was to determine the seasonal mobility of boron and salt in the soil in relation to rainfall during the 2010 growing season. Measurements were taken at ten sites, across five farms between Ballidu and Cadoux, Western Australia. Movement of salt and boron was recorded, at three soil depths to 50 cm, across the growing season at monthly intervals (2-weekly during the break of season). Salinity, on average, decreased from the first sample date in March to the final reading in September; although there were large fluctuations at 0-2 cm. Salinity levels were highest in the top 0-2 cm soil samples. Boron concentrations were on average highest at soil depths of 25-50 cm and were also found to fluctuate more at higher concentrations than at lower concentrations. Boron showed less variation than salinity across the season with no significant decrease in concentration over the growing season. The dry 2010 growing season resulted in less leaching of minerals through the soil profile than previously reported. Some leaching of salt was observed, but was mainly restricted to the top 0-25 cm. The rainfall received across the season was not sufficient to cause the leaching of boron.